Recent Applications of Cyclopropane-Based Strategies to Natural Product Synthesis - Tang, Pei; Qin, Yong (Synthesis, 2012)
Activated cyclopropanes show versatile reactivity and are therefore powerful building blocks in organic chemistry and natural product synthesis. This review focuses on recent applications of cyclopropane-based approaches to the syntheses of natural products. These applications include diverse processes involving cyclopropanation–ring-opening–cyclization or ring expansion to form key natural product skeletons.1 Introduction2 Formal Cycloaddition Strategies2.1 Formal [3+2] Cycloaddition with Aldehydes and Ketones2.2 Formal [4+3] Cycloaddition via Cope Rearrangement2.3 Cycloaddition with Transition Metals3 Cyclopropanation–Ring-Opening Strategies4 Cyclopropanation–Ring-Opening–Cyclization Strategies5 Ring Closing via Cyclopropanation6 Conclusion
Keywords: cyclopropanes; cyclopropanation; ring opening; total synthesis; natural products